Analisis Pesan Dakwah Islam Melalui Channel Youtube Ustadz Das'ad Latif - Izzudin Hitimala (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
The purpose of this research is to obtain information about Ustadz Das'ad Latif. Apart from that, researchers also want to know the method of delivering Ustadz Das'ad Latif's preaching on Ustadz Das'ad Latif's YouTube channel to students of the Department of Communication and Islamic Broadcasting, Faculty of Da'wah and Communication, UIN North Sumatra. The research results show that; That is the content of the da'wah message conveyed by Ustadz Das'ad Latif, motivation, advice, warnings which are packaged in the form of videos which are embellished by choosing adaptive sentences so that they can be easily accepted and understood by students. The method of delivering Ustadz Das'ad Latif's Da'wah has a distinctive audio and visual sound that matches the way he delivers his preaching and with various themes every week. Likewise, the title of the da'wah content engages the younger generation of millennials so that students are more motivated.